Propuesta de difusión del patrimonio cultural inmaterial por medio de estrategias digitales que contribuyan al fortalecimiento de la identidad en los niños del cantón Quevedo, provincia de Los Ríos, Año 2022 - Moreira Miranda, Marcia Johanna (2022)
The present work was carried out with the purpose of to elaborate a proposal for the dissemination of immaterial cultural heritage aimed at the children of the Quevedo canton, province of Los Ríos. For the realization of this work, three specific objectives were formed. Which consisted of the elaboration of the inventory records of the most